Film-induced tourism: push and pull motivation factors of local young travelers to visit film locations in Malaysia - Khairi, Nadiah; Saad, Mazni (2020)
The main objectives of this research is to identify the push and pull motivation factors that give the most contribution towards visiting the film locations and also to identify the pattern of film-watching habits that influence local young travelers to visit the film locations in Malaysia. The theory of push and pull factors was adopted from previous study and discussed in detail in this research. Data collected aiming the responses from Malaysian young travelers aged 15 to 30 all around in Malaysia. The sampling techniques being used in this research were through convenience and snowball sampling method by using the electronic questionnaire. Targeted respondents in the research was 384 and 189 were able to be collected through pilot testing. The result from this research discovered that there were several of push and pull motivation factors that inducing local young travelers to visit the film locations in Malaysia. Findings show that unique experience gives the most impact in push factors in explaining young travelers to visit the film locations while for pull factors are the entertainment. Last but not least, the pattern of film-watching habit, obtained from local young travelers also can contribute towards the better film study and enhance the film as a powerful marketing in attracting more domestic and international tourists through films and dramas.